2020
DOI: 10.3390/v12060601
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inducible Prophage from Burkholderia vietnamiensis G4 Is Widely Distributed across the Species and Has Lytic Activity against Pathogenic Burkholderia

Abstract: Burkholderia species have environmental, industrial and medical significance, and are important opportunistic pathogens in individuals with cystic fibrosis (CF). Using a combination of existing and newly determined genome sequences, this study investigated prophage carriage across the species B. vietnamiensis, and also isolated spontaneously inducible prophages from a reference strain, G4. Eighty-one B. vietnamiensis genomes were bioinformatically screened for prophages using PHASTER (Phage Search Tool Enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
3
2
0
Order By: Relevance
“…Our findings demonstrate that clinically significant Burkholderia isolates host a variety of prophage elements, in agreement with previous studies, showing that lysogeny is relatively common in this genus [ 3 , 49 , 50 ]. While our study was likely underpowered to identify a strong correlation between prophage abundance and phage susceptibility, we found more prophages and greater overall phage resistance in B. multivorans isolates compared to B. cenocepacia isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings demonstrate that clinically significant Burkholderia isolates host a variety of prophage elements, in agreement with previous studies, showing that lysogeny is relatively common in this genus [ 3 , 49 , 50 ]. While our study was likely underpowered to identify a strong correlation between prophage abundance and phage susceptibility, we found more prophages and greater overall phage resistance in B. multivorans isolates compared to B. cenocepacia isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings demonstrate that clinically significant Burkholderia isolates are host to a variety of prophage elements, in agreement with previous studies showing that lysogeny is relatively common in this genus (2), ( 47), (16). We found that a higher overall abundance of prophages did not correlate with phage susceptibility in our dataset.…”
Section: Discussionsupporting
confidence: 92%
“…Small differences in host range within each group of phages could be attributed to differences in titer of the lysate stocks. Notably, with the exception of BCC05 and BCC06, lytic host-range of bacteriophages of prophage origin were comparable to those of environmental origin, both within our study (comparing BCC02-BCC08 with BCh7 and DSMZ107315) and in the literature (16,47).…”
Section: Aim 2: Host Range Screensupporting
confidence: 81%
See 1 more Smart Citation
“…The B. vietnamiensis G4 capacity to survive harmful compounds in contaminated areas allowed its use in bioremediation experiments, combined with high-performance sequencing techniques and transcription analysis, which enabled the identification of genes differently expressed in its genome [ 23 , 25 27 ] and its functions in the biodegradation process [ 28 31 ]. The use of new high-performance sequencing tools and transcriptome analysis is important to help us understand microorganism responses under different stress conditions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%